Effects of Tapping and Stimulation Frequency on Performance of Yield and Selected Latex Physiological Parameters of Rubber (Hevea Brasiliensis Muell.Arg.) Clones RRIM 600 and Gt 1 - Thanh, Do Kim (1995)
Three experiments were conducted on two rubber clones to study the effects of tapping and stimulation frequency on performance of yield and some selected latex physiological parameters. The first experiment studied the long-term effects of various frequencies of 2.5% ethephon stimulation on yield performance of RRIM 60 0 over 14 years duration. The second experiment investigated the various combinations of tapping and stimulation frequency on the yield performance of GT 1. over 14 years duration. A short-term experiment of four years constituted the third experiment which studied the effects of tapping and stimulation frequency on performance of yield, some selected latex physiological parameters and bark characteristics of RRIM 600.